Lonely planet west africa - Bewer, Tim.; Carillet, Jean-Bernard.; Clammer, Paul.; Filou, Emilie; Grosberg, Michael; Ham, Anthony; Kane, Katharina; Karlin, Adam.; Masters, Tom.; Thomas, Kate. ([S.l.] : Lonely Planet, 2009)
Experience the best of West Africa with Lonely Planet. With our 7th edition you'll discover the varied landscape of this fascinating region - take a slow boat to Timbuktu, camp under the Sahara's starry skies, hike through ancient Dogon Country, discover Cote d'Ivoire's cosmopolitan Abidjan and kick-back on Ghana's palm-fringed beaches. Lonely Planet guides are written by experts who get to the heart of every destination they visit. This fully updated edition is packed with accurate, practical and honest advice, designed to give you the information you need to make the most of your trip. In This Guide: Essential safety information provided throughout Unrivalled activities and courses information for the whole region Green Index to make your travels ecofriendly.
Keywords: Africa, French-speaking Western; Africa, West